A kind of heteropoly compound and its preparation method and use

The heteromulti-compound catalyst is prepared by microwave reaction and step-by-step calcination in the catalyst for preparing methacrylic acid oxidation, which solves the problems of low activity and selectivity, complex process, high cost and poor stability in the prior art, and achieves the effects of high reaction activity and selectivity, process simplification and cost reduction.

CN116196955BActive Publication Date: 2025-04-15SHANGHAI HUAYI NEW MATERIAL
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310270583.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2025-04-15
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

The prior art has problems such as low activity and selectivity, complex process, high cost and poor stability in the catalyst for preparing methacrylic acid by oxidation of methacrylic acid.

Method used

A heteromulti-compound catalyst is prepared by microwave reaction and step-by-step calcination. A catalyst with high reactivity and selectivity is obtained by mixing compounds of Mo, V, P, Ag, X, Y, and Z, microwave reaction, adding a thermal conductivity agent to form and step-by-step calcination.

Benefits of technology

Under relatively mild reaction process conditions, high reaction activity and methacrylic acid selectivity are achieved, the process flow is simplified, the cost is reduced, and the stability of the catalyst is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004134467830000131
    Figure BDA0004134467830000131
Patent Text Reader

Abstract

A heteropoly compound and its preparation method and use. Provided is a heteropoly compound having the following composition: x(Mo a V b P c Ag d X e Y f Z g O h ) / yM; the heteropoly compound is prepared by a method comprising the following steps: (1) mixing compounds containing Mo, V, P, Ag, X, Y, and Z to obtain a mixture; (2) subjecting the mixture to a microwave reaction for 0.1-5.0h; (3) forming after adding a thermal conductive agent; (4) calcining the formed sample in steps to obtain a final catalyst product, wherein the calcination in steps comprises: a first step: calcining at 150-300°C and an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is 5-30%; a second step: calcining at 300-440°C and an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is higher than that of the first step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of catalysts, and in particular relates to a heteropoly compound and a preparation method thereof, as well as use of the heteropoly compound as a catalyst for oxidizing methacrolein to prepare methacrylic acid. Background Art

[0002] Methacrylic acid (MAA) is an important organic chemical raw material and monomer of polymers, mainly used for the production of polymethyl methacrylate (PMMA, organic glass), and is also widely used in organic coatings, plastic modifiers, ion exchange resins and adhesives. At present, there are successful industrial examples of using heteropoly compounds as catalysts to oxidize C4 raw materials mainly composed of tert-butyl alcohol or isobutylene into the second step of methacrylic acid, that is, oxidizing methacrolein to methacrylic acid, but there are still problems such as complex preparation process, low activity and selectivity, easy loss of active components and poor stability, and short life. There are also corresponding patent literature studies on the preparation method of the heteropoly compounds used in the reaction.

[0003] Patent US3761516 uses a material with a macroporous structure as a carrier, and loads molybdenum, phosphorus, and arsenic as the main active ingredients, and aluminum, copper, and cobalt as cocatalysts, but the specific surface area of ​​the supported catalyst is not high, and the activity of the catalyst needs to be improved. Chinese patent CN103861640 B discloses a heteropolyacid catalyst and a preparation method thereof, containing phosphorus, molybdenum, vanadium, copper, and arsenic as necessary active components, and using a composition of cuprous oxide and copper phosphate as all or part of the copper-containing material of the heteropolyacid catalyst. Patent CN112675912A discloses a preparation method for a catalyst for the production of unsaturated carboxylic acids, wherein the catalyst includes active components of molybdenum, phosphorus, vanadium, copper, arsenic, and tungsten, and after the active powder and the molding aid are mixed and crushed, they are coated on an inert carrier with the participation of a binder, and the amount of the binder used is reduced by introducing a molding aid, and the strength of the catalyst is thereby improved, but its preparation process is relatively complicated and the process is long. Patent CN114160201A provides a heteropoly acid catalyst, which is a heteropoly compound containing elements such as phosphorus, molybdenum, vanadium, arsenic, copper, and cesium, and has high reactivity and selectivity for the oxidation reaction of methacrolein to methacrylic acid, but the catalyst preparation cost is very high, and the preparation process is very long (reflux reaction for 13 hours, stirring for 4 hours, and constant temperature aging for 6 hours), which is not conducive to the large-scale and stable preparation of the catalyst. Therefore, it is considered to improve the preparation process of the heteropoly compound on the basis of the existing technology to improve the activity and selectivity of the heteropoly compound as a catalyst in the reaction of methacrolein oxidation to methacrylic acid. Summary of the invention

[0004] The present application provides a heteropoly compound and a preparation method thereof, wherein a microwave reaction and a step-by-step calcination method are used in the preparation process to obtain good catalytic reaction performance. The present application also provides a use of the heteropoly compound to oxidize methacrolein to prepare methacrylic acid, and when the heteropoly compound is used as a catalyst to oxidize methacrolein to prepare methacrylic acid, high reaction activity and methacrylic acid selectivity can be obtained under relatively mild reaction process conditions.

[0005] One aspect of the present application provides a heteropoly compound having the following composition:

[0006] x(Mo a V b P c Ag d X e Y f Z g O h ) / yM

[0007] Wherein, x and y represent the amount of the main catalyst and the thermal conductor M, y / x = 10 -50wt%;

[0008] X represents at least one of Si, Ge, Sb, Pb, Fe, and Pd,

[0009] Y represents at least one of K, Cs, Ca, Mg, Ba, Re, Ru, and Rh,

[0010] Z represents at least one of Ni, Cu, Zn, Au, Nb and Ta,

[0011] M refers to the heating agent;

[0012] a, b, c, d, e, f, g, h represent the molar numbers of Mo, V, P, Ag, X, Y, Z and O respectively, when a=12, b=0.1-3.0, c=0.1-3.0, d=0.01-2.0, e=0.01-2.0, f=0.01-2.0, g=0.1-2.0, h is the molar number of oxygen atoms required to satisfy the above-mentioned atomic valence states;

[0013] The heteropoly compound is prepared by a method comprising the following steps:

[0014] (1) mixing compounds containing Mo, V, P, Ag, X, Y, and Z to obtain a mixture;

[0015] (2) subjecting the above mixture to microwave reaction for 0.1-5.0 h;

[0016] (3) Forming after adding thermal conductive agent;

[0017] (4) calcining the formed sample in steps to obtain the final catalyst product.

[0018] The step-by-step roasting comprises:

[0019] The first step: calcining at 150-300°C in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is 5-30%;

[0020] The second step is calcining at 300-440° C. in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is higher than that of the first step.

[0021] Another aspect of the present application is to provide a method for preparing a heteropoly compound, wherein the heteropoly compound has the following composition:

[0022] x(Mo a V b P c Ag d X e Y f Z g O h ) / yM

[0023] Wherein, x and y represent the amount of the main catalyst and the thermal conductor M, y / x = 10-50wt%;

[0024] X represents at least one of Si, Ge, Sb, Pb, Fe, and Pd,

[0025] Y represents at least one of K, Cs, Ca, Mg, Ba, Re, Ru, and Rh,

[0026] Z represents at least one of Ni, Cu, Zn, Au, Nb and Ta,

[0027] M refers to the heating agent;

[0028] a, b, c, d, e, f, g, h represent the molar numbers of Mo, V, P, Ag, X, Y, Z and O respectively, when a=12, b=0.1-3.0, c=0.1-3.0, d=0.01-2.0, e=0.01-2.0, f=0.01-2.0, g=0.1-2.0, h is the molar number of oxygen atoms required to satisfy the above-mentioned atomic valence states;

[0029] The method comprises the following steps:

[0030] (1) mixing compounds containing Mo, V, P, Ag, X, Y, and Z to obtain a mixture;

[0031] (2) subjecting the above mixture to microwave reaction for 0.1-5.0 h;

[0032] (3) Forming after adding thermal conductive agent;

[0033] (4) calcining the formed sample in steps to obtain the final catalyst product.

[0034] The step-by-step roasting comprises:

[0035] The first step: calcining at 150-300°C in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is 5-30%;

[0036] The second step is calcining at 300-440° C. in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is higher than that of the first step. DETAILED DESCRIPTION

[0037] Unless otherwise stated herein, the reactions are all carried out at room temperature and pressure.

[0038] In this document, unless otherwise specified, the amounts of materials are all based on weight.

[0039] Herein, unless otherwise specified, the reaction steps may be performed sequentially, in any order or simultaneously.

[0040] In this document, unless otherwise specified, all parts, contents, percentages, concentrations, etc. represent parts by weight, contents by weight, percentages by weight, concentrations by weight, etc.

[0041] As used herein, the sum of all percentages of components in a mixture or composition is 100%, unless otherwise stated.

[0042] One aspect of the present application provides a heteropoly compound having the following composition:

[0043] x(Mo a V b P c Ag d X e Y f Z g O h ) / yM

[0044] Wherein, x and y represent the amount of the main catalyst and the thermal conductor M, y / x = 10-50wt%;

[0045] X represents at least one of Si, Ge, Sb, Pb, Fe, and Pd,

[0046] Y represents at least one of K, Cs, Ca, Mg, Ba, Re, Ru, and Rh,

[0047] Z represents at least one of Ni, Cu, Zn, Au, Nb and Ta,

[0048] M refers to the heating agent;

[0049] a, b, c, d, e, f, g, h represent the molar numbers of Mo, V, P, Ag, X, Y, Z and O respectively, when a=12, b=0.1-3.0, c=0.1-3.0, d=0.01-2.0, e=0.01-2.0, f=0.01-2.0, g=0.1-2.0, h is the molar number of oxygen atoms required to satisfy the above-mentioned atomic valence states;

[0050] The heteropoly compound is prepared by a method comprising the following steps:

[0051] (1) mixing compounds containing Mo, V, P, Ag, X, Y, and Z to obtain a mixture;

[0052] (2) subjecting the above mixture to microwave reaction for 0.1-5.0 h;

[0053] (3) Forming after adding thermal conductive agent;

[0054] (4) calcining the formed sample in steps to obtain the final catalyst product.

[0055] The step-by-step roasting comprises:

[0056] The first step: calcining at 150-300°C in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is 5-30%;

[0057] The second step is calcining at 300-440° C. in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is higher than that of the first step.

[0058] In one example of the present application, y / x is 15-40 wt %, preferably 15-30 wt %, and more preferably 20 wt %.

[0059] In one example of the present application, X refers to at least one of Si, Ge, Sb, Pb, Fe, and Pd. Preferably, X is selected from Si, Ge, Sb, Fe, and combinations thereof, for example, X is selected from Sb, Fe, and combinations thereof.

[0060] In one example of the present application, Y refers to at least one of K, Cs, Ca, Mg, Ba, Re, Ru, and Rh. Preferably, Y is selected from K, Cs, Ca, Mg, Ba, and combinations thereof, for example, Y is selected from K, Cs, and combinations thereof.

[0061] In one example of the present application, Z refers to at least one of Ni, Cu, Zn, Au, Nb, and Ta. Preferably, Z is selected from Ni, Cu, Zn, and combinations thereof, for example, Z is selected from Cu.

[0062] In one example of the present application, M refers to a heat guide agent, including but not limited to a mixture of one or more of Al2O3, SiC, SiO2, CaCO3, MoO3, WO3, TiO2 or ZrO2, preferably a mixture of one or more of SiC, CaCO3, MoO3 or ZrO2, more preferably SiC, CaCO3 and a mixture thereof.

[0063] In the present application, a, b, c, d, e, f, g, and h represent the molar numbers of Mo, V, P, Ag, X, Y, Z, and O, respectively. When a=12, b=0.1-3.0, c=0.1-3.0, d=0.01-2.0, e=0.01-2.0, f=0.01-2.0, g=0.1-2.0, and h is the molar number of oxygen atoms required to satisfy the above-mentioned atomic valence states.

[0064] When a=12, b may be, for example, 0.1-3.0, preferably 0.2-2.0, more preferably 0.3-1.5, still more preferably 0.4-1.0, most preferably 0.5-0.8.

[0065] When a=12, c may be, for example, 0.1-3.0, preferably 0.2-2.5, more preferably 0.4-2.0, still more preferably 0.5-1.6, most preferably 0.8-1.2.

[0066] When a=12, d may be, for example, 0.01-2.0, preferably 0.05-1.5, more preferably 0.08-1.0, still more preferably 0.1-0.6, most preferably 0.15-0.4.

[0067] When a=12, e may be, for example, 0.01-2.0, preferably 0.05-1.5, more preferably 0.08-1.0, still more preferably 0.1-0.6, most preferably 0.15-0.4.

[0068] When a=12, f may be, for example, 0.01-2.0, preferably 0.05-1.5, more preferably 0.1-1.2, still more preferably 0.3-1.0, most preferably 0.4-0.8.

[0069] When a=12, g may be, for example, 0.01-2.0, preferably 0.05-1.5, more preferably 0.08-1.0, still more preferably 0.1-0.6, most preferably 0.15-0.5.

[0070] Another aspect of the present application provides a method for preparing a heteropoly compound, wherein the heteropoly compound has the following composition:

[0071] x(Mo a V b P c Ag d Xe Y f Z g O h ) / yM

[0072] Wherein, x and y represent the amount of the main catalyst and the thermal conductor M, y / x = 10-50wt%;

[0073] X represents at least one of Si, Ge, Sb, Pb, Fe, and Pd,

[0074] Y represents at least one of K, Cs, Ca, Mg, Ba, Re, Ru, and Rh,

[0075] Z represents at least one of Ni, Cu, Zn, Au, Nb and Ta,

[0076] M refers to the heating agent;

[0077] a, b, c, d, e, f, g, h represent the molar numbers of Mo, V, P, Ag, X, Y, Z and O respectively, when a=12, b=0.1-3.0, c=0.1-3.0, d=0.01-2.0, e=0.01-2.0, f=0.01-2.0, g=0.1-2.0, h is the molar number of oxygen atoms required to satisfy the above-mentioned atomic valence states;

[0078] The method comprises the following steps:

[0079] (1) mixing compounds containing Mo, V, P, Ag, X, Y, and Z to obtain a mixture;

[0080] (2) subjecting the above mixture to microwave reaction for 0.1-5.0 h;

[0081] (3) Forming after adding thermal conductive agent;

[0082] (4) calcining the formed sample in steps to obtain the final catalyst product.

[0083] The step-by-step roasting comprises:

[0084] The first step: calcining at 150-300°C in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is 5-30%;

[0085] The second step is calcining at 300-440° C. in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is higher than that of the first step.

[0086] In the method of the present application, the compounds of Mo, V, P, Ag, X, Y, and Z can be precursor compounds commonly used in the art for forming catalysts. Nitrates, carbonates, acetates, oxides, halides, oxides, oxyacid salts, etc. of the elements constituting the catalyst can be used.

[0087] Suitable Mo compounds (Mo precursor compounds) can be compounds commonly used in the art, including but not limited to acid compounds such as molybdic acid, phosphomolybdic acid, and silicomolybdic acid; oxides such as molybdenum dioxide and molybdenum trioxide; or at least one of molybdates (such as nitrates, acetates, or ammonium salts) such as ammonium molybdate and ammonium permolybdate.

[0088] Suitable V compounds (V precursor compounds) may be compounds commonly used in the art, including but not limited to at least one of ammonium vanadate, ammonium metavanadate, vanadium pentoxide, vanadium chloride, and the like.

[0089] Suitable P compounds (P precursor compounds) may be compounds commonly used in the art, including but not limited to at least one of phosphates such as phosphoric acid, ammonium phosphate, and cesium phosphate, and oxides such as phosphorus pentoxide.

[0090] Suitable Ag compounds (Ag precursor compounds) may be compounds commonly used in the art, including but not limited to at least one of silver phosphate, silver acetate, silver chloride, and the like.

[0091] Suitable X, Y, Z compounds (precursor compounds of X, Y, Z) may include at least one of nitrates, acetates, chlorides or oxides, etc. For example, X, Y, Z compounds include but are not limited to antimony trioxide, cesium nitrate, copper nitrate, iron nitrate, potassium nitrate and combinations thereof.

[0092] In one example of the present application, the compounds of Mo, V, P, Ag, X, Y, and Z can be mixed in a solvent. The solvent can be a commonly used solvent in the art, including but not limited to water or organic solvents such as ethanol and acetone, or acids such as hydrochloric acid and nitric acid. The solvent is preferably water. The amount of the solvent is not specifically limited, as long as the compounds can be uniformly mixed.

[0093] The order of mixing the compounds of Mo, V, P, Ag, X, Y, and Z can be arbitrary. However, in order to obtain a catalyst with better performance, it is preferred to mix the compounds of Mo, V, P, and Ag (or their solutions) first, and then add the compounds of X, Y, and Z (or their solutions).

[0094] In one embodiment of the present application, the mixing in step (1) of the method can be stirred to make the dispersion more uniform, and the mixing temperature is generally 40-150° C., preferably 60-120° C. Considering the influence of the solvent, the temperature is more preferably 80-120° C. The mixing time can be selected from 1.0-12.0 hours, more preferably 2.0-4.0 hours.

[0095] In step (2) of the method of the present application, the microwave can be selected from a high-temperature or normal-temperature microwave platform, with a microwave power of 200-800 W (preferably 400-800 W, more preferably 600 W), a temperature of 30-200° C. (preferably 40-150° C., more preferably 60-100° C.), and a microwave reaction time of 0.1-5.0 h (preferably 0.2-4.0 h, more preferably 0.4-3.0 h, even more preferably 0.5-2.0 h, and most preferably 0.8-1.5 h).

[0096] After microwave reaction, the mixture forms an aqueous solution or slurry. The aqueous solution or slurry can be dried. The specific drying method is not particularly limited, including but not limited to spray drying, oven drying, rotary drying or vacuum drying, etc., preferably spray drying. The drying temperature is usually 60-140°C, preferably 80-120°C.

[0097] In step (3) of the present application, in addition to the thermal conductor, a binder may be optionally added. The binder may be a commonly used binder in the art, including but not limited to at least one of ethanol, polyethylene glycol, chitin, methyl cellulose, etc., preferably ethanol and polyethylene glycol. The amount of binder added is not specifically limited, for example, the amount of binder added may account for 1-10% of the mass of the catalyst active component, preferably 4-8%. In step (3), the molding method is not particularly limited, and any conventional molding method known in the art may be used, including extrusion molding, compression molding, spray molding, etc., preferably compression molding.

[0098] In step (4) of the present application, the stepwise calcination includes a first step: calcination at 150-300° C. and an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is 5-30%. The calcination temperature is preferably 180-280° C., more preferably 200-250° C. The calcination time is not specifically limited, and may be, for example, 1-4 hours, preferably 1.5-3.5 hours, more preferably 1.8-3 hours. The volume percentage of oxygen is preferably 5-20%, more preferably 5-15%.

[0099] The stepwise calcination includes a second step: calcination at 300-440°C and an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is higher than that of the first step. The calcination temperature is preferably 320-440°C, more preferably 350-400°C. The calcination time is not specifically limited, and may be, for example, 1-10 hours, preferably 2-8 hours, and more preferably 4-7 hours. The volume percentage of oxygen is higher than that of the first step, for example, the volume percentage of oxygen may be 20-50%, for example 30-50%, and more preferably 30-40%.

[0100] The heteropoly compound prepared in the present application may not contain arsenic and arsenic compounds, which reduces the use of toxic substances and advocates and supports green chemistry. In the preparation process of the catalyst, microwave reaction is used to accelerate the aging rate of the solution or slurry, so that the precursor solution or slurry can be made uniform and the active components can be well dispersed. By adopting staged roasting in an atmosphere with different oxygen contents, the components can be gradually oxidized to the required valence state and combined into the required active sites, thereby improving the performance of the catalyst. The heteropoly compound has good activity and selectivity in the reaction of selective oxidation of methacrolein to prepare methacrylic acid.

[0101] The present application also provides a use of the prepared heteropoly compound for the oxidation of methacrolein to prepare methacrylic acid. The heteropoly compound prepared by the above specific method can be used as a catalyst in the reaction of oxidative preparation of methacrylic acid. The catalytic oxidation reaction includes the following process: the methacrolein raw material, oxygen-containing gas, diluent gas and water vapor are preheated and mixed, and then introduced into a fixed bed tubular reactor filled with the heteropoly compound prepared by the above specific method to prepare methacrylic acid under certain reaction conditions. The molar fraction of the methacrolein raw material is preferably 3-10%. The oxygen-containing gas may include pure oxygen, oxygen-rich gas or air, and the molar ratio of oxygen to the raw material methacrolein is preferably 1-8, more preferably 2-4. The diluent gas may include at least one of nitrogen, carbon monoxide, carbon dioxide or water vapor, and the molar ratio of the diluent gas to the raw material methacrolein is preferably 2.0-10.0, more preferably 3.0-8.0. Under the certain reaction conditions, the reaction temperature is preferably 200-300°C, more preferably 220-280°C; the reaction space velocity is preferably 1000-5000h -1 , more preferably 1200-3000h -1 .

[0102] Some specific examples and comparative examples are given below to further illustrate the present invention, but the present invention is not limited to these examples and comparative examples. The analysis and testing of the reactants and products uses gas chromatography. The conversion rate of methacrolein and the selectivity of methacrylic acid in the reaction are calculated as follows:

[0103] Methacrolein conversion rate (%) = (amount of methacrolein consumed / amount of methacrolein in raw material) × 100%

[0104] Methacrylic acid selectivity (%) = (amount of methacrylic acid produced / amount of methacrolein consumed) × 100%

[0105] Example 1

[0106] 1) Preparation of catalyst

[0107] Add 100g of ammonium heptamolybdate aqueous solution, 5.31g of ammonium metavanadate solution, 2.55g of silver nitrate solution and 8.64g of 85% orthophosphoric acid solution to 200g of pure water. Then add 2.21g of antimony trioxide in tartaric acid solution, 8.85g of cesium nitrate solution and 5.28g of copper nitrate solution in sequence. Stir and reflux at 100°C for 2.0h. The above solution or slurry is subjected to microwave reaction for 1.0h, with a microwave temperature of 80°C and a power of 600W. The obtained liquid is spray-dried at 60-140°C to obtain a solid heteropoly compound active ingredient. Add 10% SiC, 10% CaCO3 and 4% polyethylene glycol by weight of the solid active component and form it using a tablet forming machine. In addition to H and O, the composition of the heteropoly compound is Mo 12 V 0.6 P 1.0 Ag 0.2 Sb 0.2 Cs 0.6 Cu 0.3 / 10%SiC10%CaCO3. Baking at 220°C with 10% oxygen for 2 hours, and baking at 380°C with 30% oxygen for 6 hours to obtain a heteropoly compound catalyst.

[0108] 2) Evaluation of reaction performance

[0109] The raw material gas consisting of 4.7% methacrolein, 9.8% oxygen, 37.4% nitrogen and water vapor was charged into a fixed bed tubular reactor by using the heteropoly compound as a catalyst, and reacted at 250°C, normal pressure and a contact time of 2.9 seconds. The reaction results are shown in Table 1.

[0110] Comparative Example 1

[0111] 1) Preparation of catalyst

[0112] In 200g of pure water, add 100g of ammonium heptamolybdate aqueous solution, 5.31g of ammonium metavanadate solution, 2.55g of silver nitrate solution and 8.64g of 85% orthophosphoric acid solution. Then add 2.21g of antimony trioxide in tartaric acid solution, 8.85g of cesium nitrate solution and 5.28g of copper nitrate solution in sequence. Stir and reflux at 100°C for 2.0h. Spray dry the obtained liquid at 60-140°C to obtain the active ingredient of the solid heteropoly compound. Add 10% SiC, 10% CaCO3 and 4% polyethylene glycol by weight of the solid active component and form it using a tablet forming machine. In addition to H and O, the composition of the heteropoly compound is Mo 12 V 0.6 P 1.0 Ag 0.2 Sb 0.2 Cs 0.6 Cu0.3 / 10% SiC 10% CaCO3. The catalyst was calcined at 220°C with 10% oxygen for 2 hours and then calcined at 380°C with 30% oxygen for 6 hours to obtain a heteropoly compound catalyst.

[0113] 2) Evaluation of reaction performance

[0114] The raw material gas consisting of 4.7% methacrolein, 9.8% oxygen, 37.4% nitrogen and water vapor was charged into a fixed bed tubular reactor by using the heteropoly compound as a catalyst, and reacted at 260°C, normal pressure and a contact time of 2.9 seconds. The reaction results are shown in Table 1.

[0115] Comparative Example 2

[0116] 1) Preparation of catalyst

[0117] In 200g of pure water, add 100g of ammonium heptamolybdate aqueous solution, 5.31g of ammonium metavanadate solution, 2.55g of silver nitrate solution and 8.64g of 85% orthophosphoric acid solution. Then add 2.21g of antimony trioxide in tartaric acid solution, 8.85g of cesium nitrate solution and 5.28g of copper nitrate solution in sequence. Stir and reflux at 100°C for 2.0h. The above solution or slurry is subjected to microwave reaction for 1.0h, the microwave temperature is 80°C, the power is 600W, and the obtained liquid is spray-dried at 60-140°C to obtain the active ingredient of the solid heteropoly compound. Add 10% SiC, 10% CaCO3 and 4% polyethylene glycol by weight of the solid active component, and form it using a tablet forming machine. In addition to H and O, the active composition of the heteropoly compound is Mo 12 V 0.6 P 1.0 Ag 0. 2Sb 0.2 Cs 0.6 Cu 0.3 / 10% SiC10% CaCO3. 10% oxygen was introduced and the mixture was calcined at 220°C for 2 hours and at 380°C for 6 hours to obtain a heteropoly compound catalyst.

[0118] 2) Evaluation of reaction performance

[0119] The raw material gas consisting of 4.7% methacrolein, 9.8% oxygen, 37.4% nitrogen and water vapor was charged into a fixed bed tubular reactor by using the heteropoly compound as a catalyst, and reacted at 260°C, normal pressure and a contact time of 2.9 seconds. The reaction results are shown in Table 1.

[0120] Example 2

[0121] 1) Preparation of catalyst

[0122] In 200g of pure water, add 100g of ammonium heptamolybdate aqueous solution, 5.31g of ammonium metavanadate solution, 2.55g of silver nitrate solution and 8.64g of 85% orthophosphoric acid solution. Then add 6.33g of ferric nitrate solution, 8.85g of cesium nitrate solution and 5.28g of copper nitrate solution in sequence. Stir and reflux at 100°C for 2.0h. The above solution or slurry is subjected to microwave reaction for 1.0h, the microwave temperature is 80°C, the power is 600W, and the obtained liquid is spray-dried at 60-140°C to obtain the active ingredient of the solid heteropoly compound. Add 10% SiC, 10% CaCO3 and 4% polyethylene glycol by weight of the solid active component, and form it using a tablet forming machine. In addition to H and O, the composition of the heteropoly compound is Mo 12 V 0.6 P 1.0 Ag 0.2 Fe 0.2 Cs 0.6 Cu 0.3 / 10% SiC10% CaCO3. Calcination, passing 10% oxygen at 220°C for 2 hours, and passing 30% oxygen at 380°C for 6 hours to obtain a heteropoly compound catalyst.

[0123] 2) Evaluation of reaction performance

[0124] The raw material gas consisting of 4.7% methacrolein, 9.8% oxygen, 37.4% nitrogen and water vapor was charged into a fixed bed tubular reactor by using the heteropoly compound as a catalyst, and reacted at 250°C, normal pressure and a contact time of 2.9 seconds. The reaction results are shown in Table 1.

[0125] Comparative Example 3

[0126] 1) Preparation of catalyst

[0127] In 200g of pure water, add 100g of ammonium heptamolybdate aqueous solution, 5.31g of ammonium metavanadate solution, 2.55g of silver nitrate solution and 8.64g of 85% orthophosphoric acid solution. Then add 2.71g of 88% arsenic acid solution, 8.85g of cesium nitrate solution and 5.28g of copper nitrate solution in sequence. Stir and reflux at 100°C for 2.0h. The above solution or slurry is subjected to microwave reaction for 1.0h, the microwave temperature is 80°C, the power is 600W, and the obtained liquid is spray-dried at 60-140°C to obtain the active ingredient of the solid heteropoly compound. Add 10% SiC, 10% CaCO3 and 4% polyethylene glycol by weight of the solid active component, and form it using a tablet forming machine. In addition to H and O, the composition of the heteropoly compound is Mo 12 V 0.6 P 1.0 Ag 0.2 As0.2 Cs 0.6 Cu 0.3 / 10% SiC 10% CaCO3. Calcination, passing 10% oxygen at 220°C for 2 hours, and passing 30% oxygen at 380°C for 6 hours to obtain a heteropoly compound catalyst.

[0128] 2) Evaluation of reaction performance

[0129] The raw material gas consisting of 4.7% methacrolein, 9.8% oxygen, 37.4% nitrogen and water vapor was charged into a fixed bed tubular reactor by using the heteropoly compound as a catalyst, and reacted at 250°C, normal pressure and a contact time of 2.9 seconds. The reaction results are shown in Table 1.

[0130] Example 3

[0131] 1) Preparation of catalyst

[0132] Add 100g of ammonium heptamolybdate aqueous solution, 5.49g of ammonium metavanadate solution, 5.27g of silver nitrate solution and 8.93g of 85% orthophosphoric acid solution to 200g of pure water. Then add 2.28g of antimony trioxide in tartaric acid solution, 1.57g of potassium nitrate solution and 7.56g of copper nitrate solution in sequence. Stir and reflux at 100°C for 2.0h. The above solution or slurry is subjected to microwave reaction for 1.0h, the microwave temperature is 80°C, the power is 600W, and the obtained liquid is spray-dried at 60-140°C to obtain the active ingredient of the solid heteropoly compound. Add 10% SiC, 10% CaCO3 and 4% polyethylene glycol by weight of the solid active component, and form it using a tablet forming machine. In addition to H and O, the composition of the heteropoly compound is Mo 12 V 0.6 P 1.0 Ag 0.4 Sb 0.2 K 0.4 Cu 0.4 / 10% SiC 10% CaCO3. The catalyst was calcined at 220°C with 10% oxygen for 2 hours and then at 380°C with 30% oxygen for 6 hours to obtain a heteropoly compound catalyst.

[0133] 2) Evaluation of reaction performance

[0134] The raw material gas consisting of 4.7% methacrolein, 9.8% oxygen, 37.4% nitrogen and water vapor was charged into a fixed bed tubular reactor by using the heteropoly compound as a catalyst, and reacted at 250°C, normal pressure and a contact time of 2.9 seconds. The reaction results are shown in Table 1.

[0135] Comparative Example 4

[0136] 1) Preparation of catalyst

[0137] Add 100g of ammonium heptamolybdate aqueous solution, 5.49g of ammonium metavanadate solution, 5.27g of silver nitrate solution and 8.93g of 85% orthophosphoric acid solution to 200g of pure water. Then add 1.57g of potassium nitrate solution and 7.56g of copper nitrate solution, and stir and reflux at 100°C for 2.0h. The above solution or slurry is subjected to microwave reaction for 1.0h, the microwave temperature is 80°C, the power is 600W, and the obtained liquid is spray-dried at 60-140°C to obtain the active ingredient of the solid heteropoly compound. Add 10% SiC, 10% CaCO3 and 4% polyethylene glycol by weight of the solid active component, and form it using a tablet forming machine. In addition to H and O, the composition of the heteropoly compound is Mo 12 V 0.6 P 1.0 Ag 0.4 K 0.4 Cu 0.4 / 10% SiC 10% CaCO3. The mixture was calcined at 220°C with 10% oxygen for 2 hours and then calcined at 380°C with 30% oxygen for 6 hours to obtain a heteropoly compound.

[0138] 2) Evaluation of reaction performance

[0139] The raw material gas consisting of 4.7% methacrolein, 9.8% oxygen, 37.4% nitrogen and water vapor was charged into a fixed bed tubular reactor by using the heteropoly compound as a catalyst, and reacted at 250°C, normal pressure and a contact time of 2.9 seconds. The reaction results are shown in Table 1.

[0140] Comparative Example 5

[0141] 1) Preparation of catalyst

[0142] Add 100g of ammonium heptamolybdate aqueous solution, 5.49g of ammonium metavanadate solution, 5.27g of silver nitrate solution and 8.93g of 85% orthophosphoric acid solution to 200g of pure water. Then add 2.28g of antimony trioxide in tartaric acid solution, 1.57g of potassium nitrate solution and 7.56g of copper nitrate solution in sequence. Stir and reflux at 100°C for 2.0h. Spray dry the obtained liquid at 60-140°C to obtain the active ingredient of the solid heteropoly compound. Add 10% SiC, 10% CaCO3 and 4% polyethylene glycol and form it using a tablet forming machine. In addition to H and O, the composition of the heteropoly compound is Mo 12 V 0.6 P 1.0 Ag 0.4 Sb 0.2 K 0.4 Cu 0.4 / 10%SiC10%CaCO3, calcined at 380℃ with air for 6 hours to obtain a heteropoly compound catalyst.

[0143] 2) Evaluation of reaction performance

[0144] The raw material gas consisting of 4.7% methacrolein, 9.8% oxygen, 37.4% nitrogen and water vapor was charged into a fixed bed tubular reactor by using the heteropoly compound as a catalyst, and reacted at 270°C, normal pressure and a contact time of 2.9 seconds. The reaction results are shown in Table 1.

[0145] Table 1 Reaction results

[0146]

Claims

1. A heteropoly compound having the following composition: x(Mo a V b P c Ag d X e Y f Z g O h ) / yM Wherein, x and y represent the amount of the main catalyst and the thermal conductor M, y / x = 10-50wt%; X represents at least one of Si, Ge, Sb, Pb, Fe, and Pd, Y represents at least one of K, Cs, Ca, Mg, Ba, Re, Ru, and Rh, Z represents at least one of Ni, Cu, Zn, Au, Nb and Ta, M refers to the heating agent; a, b, c, d, e, f, g, h represent the molar numbers of Mo, V, P, Ag, X, Y, Z and O respectively. When a = 12, b = 0.1-3.0, c = 0.1-3.0, d = 0.01-2.0, e = 0.01-2.0, f = 0.01-2.0, g = 0.1-2.0, and h is the molar number of oxygen atoms required to satisfy the above atomic valence states; The heteropoly compound is prepared by a method comprising the following steps: (1) mixing compounds containing Mo, V, P, Ag, X, Y, and Z to obtain a mixture; (2) subjecting the above mixture to microwave reaction for 0.1-5.0 h; (3) Forming after adding thermal conductive agent; (4) The formed sample is calcined in steps to obtain the final catalyst product. The step-by-step roasting comprises: Step 1: calcining at 150-300°C in an oxygen-containing gas atmosphere, with an oxygen volume percentage of 5-30%; The second step is calcining at 300-440°C in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is higher than that of the first step.

2. The heteropoly compound according to claim 1, wherein y / x is 15-40wt%.

3. The heteropoly compound according to claim 1, wherein y / x is 15-30wt%.

4. The heteropoly compound according to claim 1, wherein y / x is 20wt%.

5. The heteropoly compound according to claim 1, wherein X is selected from Si, Ge, Sb, Fe and combinations thereof.

6. The heteropoly compound according to claim 1, wherein X is selected from Sb, Fe and combinations thereof.

7. The heteropoly compound according to claim 1, wherein Y is selected from K, Cs, Ca, Mg, Ba and combinations thereof.

8. The heteropoly compound according to claim 1, wherein Y is selected from K, Cs and combinations thereof.

9. The heteropoly compound according to claim 1, wherein Z is selected from Ni, Cu, Zn and combinations thereof.

10. The heteropoly compound as claimed in claim 1, wherein Z is selected from Cu.

11. The heteropoly compound according to claim 1, wherein M is selected from a mixture of one or more of Al2O3, SiC, SiO2, MoO3, WO3, TiO2 or ZrO2.

12. The heteropoly compound according to claim 1, wherein M is selected from one or a mixture of SiC, MoO3 or ZrO2.

13. The heteropoly compound according to claim 1, wherein M is selected from SiC.

14. The heteropoly compound according to claim 1, wherein When a = 12, b is 0.2-2.0, c is 0.2-2.5, d is 0.05-1.5, e is 0.05-1.5, f is 0.05-1.5, and g is 0.05-1.

5.

15. The heteropoly compound according to claim 1, wherein When a = 12, b is 0.3-1.5, c is 0.4-2.0, d is 0.08-1.0, e is 0.08-1.0, f is 0.1-1.2, and g is 0.08-1.

0.

16. The heteropoly compound according to claim 1, wherein When a = 12, b is 0.4-1.0, c is 0.5-1.6, d is 0.1-0.6, e is 0.1-0.6, f is 0.3-1.0, and g is 0.1-0.

6.

17. The heteropoly compound according to claim 1, wherein When a = 12, b is 0.5-0.8; c is 0.8-1.2; d is 0.15-0.4; e is 0.15-0.4; f is 0.4-0.8; g is 0.15-0.

5.

18. The heteropoly compound according to claim 1, wherein The microwave power was 200-800 W, the temperature was 30-200 °C, and the microwave reaction time was 0.1-5.0 h.

19. The heteropoly compound according to claim 1, wherein The microwave power is 400-800 W, the temperature is 40-150° C., and the microwave reaction is 0.2-4.0 h.

20. The heteropoly compound according to claim 1, wherein The microwave power is 600 W, the temperature is 60-100° C., and the microwave reaction is 0.5-2.0 h.

21. The heteropoly compound according to claim 1, wherein The microwave reaction lasts for 0.8-1.5h.

22. The heteropoly compound according to claim 1, wherein In the first step of the stepwise calcination, the calcination temperature is 180-280° C.; the calcination time is 1-4 hours; and the volume percentage of oxygen is 5-20%.

23. The heteropoly compound according to claim 1, wherein In the first step of the stepwise calcination, the calcination temperature is 200-250° C.; the calcination time is 1.5-3.5 hours; and the volume percentage of oxygen is 5-15%.

24. The heteropoly compound according to claim 1, wherein In the first step of the stepwise calcination, the calcination time is 1.8-3 hours.

25. The heteropoly compound according to claim 1, wherein In the second step of the stepwise calcination, the calcination temperature is 320-440° C.; the calcination time is 1-10 hours; and the volume percentage of oxygen is 30-50%.

26. The heteropoly compound according to claim 1, wherein In the second step of the stepwise calcination, the calcination temperature is 350-400° C.; the calcination time is 2-8 hours, and the volume percentage of oxygen is 30-40%.

27. The heteropoly compound according to claim 1, wherein In the second step of the stepwise calcination, the calcination time is 4-7 hours.

28. A method for preparing a heteropoly compound, wherein the heteropoly compound has the following composition: x(Mo a V b P c Ag d X e Y f Z g O h ) / yM Wherein, x and y represent the amount of the main catalyst and the thermal conductor M, y / x = 10-50wt%; X represents at least one of Si, Ge, Sb, Pb, Fe, and Pd, Y represents at least one of K, Cs, Ca, Mg, Ba, Re, Ru, and Rh, Z represents at least one of Ni, Cu, Zn, Au, Nb and Ta, M refers to the heating agent; a, b, c, d, e, f, g, h represent the molar numbers of Mo, V, P, Ag, X, Y, Z and O respectively. When a = 12, b = 0.1-3.0, c = 0.1-3.0, d = 0.01-2.0, e = 0.01-2.0, f = 0.01-2.0, g = 0.1-2.0, and h is the molar number of oxygen atoms required to satisfy the above atomic valence states; The method comprises the following steps: (1) mixing compounds containing Mo, V, P, Ag, X, Y, and Z to obtain a mixture; (2) subjecting the above mixture to microwave reaction for 0.1-5.0 h; (3) Forming after adding thermal conductive agent; (4) The formed sample is calcined in steps to obtain the final catalyst product. The step-by-step roasting comprises: The first step: calcining at 150-300°C in an oxygen-containing gas atmosphere, with the volume percentage of oxygen being 5-30%; The second step is calcining at 300-440°C in an oxygen-containing gas atmosphere, wherein the volume percentage of oxygen is higher than that of the first step.

29. The preparation method according to claim 28, wherein y / x is 15-40wt%.

30. The preparation method according to claim 28, wherein y / x is 15-30wt%.

31. The heteropoly compound according to claim 28, wherein y / x is 20wt%.

32. The heteropoly compound according to claim 28, wherein X is selected from Si, Ge, Sb, Fe and combinations thereof.

33. The heteropoly compound according to claim 28, wherein X is selected from Sb, Fe and combinations thereof.

34. The heteropoly compound according to claim 28, wherein Y is selected from K, Cs, Ca, Mg, Ba and combinations thereof.

35. The heteropoly compound according to claim 28, wherein Y is selected from K, Cs and combinations thereof.

36. The heteropoly compound according to claim 28, wherein Z is selected from Ni, Cu, Zn and combinations thereof.

37. The heteropoly compound of claim 28, wherein Z is selected from Cu.

38. The heteropoly compound according to claim 28, wherein M is selected from a mixture of one or more of Al2O3, SiC, SiO2, MoO3, WO3, TiO2 or ZrO2.

39. The heteropoly compound according to claim 28, wherein M is selected from one or a mixture of SiC, MoO3 or ZrO2.

40. The heteropoly compound according to claim 28, wherein M is selected from SiC.

41. The heteropoly compound of claim 28, wherein When a = 12, b is 0.2-2.0, c is 0.2-2.5, d is 0.05-1.5, e is 0.05-1.5, f is 0.05-1.5, and g is 0.05-1.

5.

42. The heteropoly compound of claim 28, wherein When a = 12, b is 0.3-1.5, c is 0.4-2.0, d is 0.08-1.0, e is 0.08-1.0, f is 0.1-1.2, and g is 0.08-1.

0.

43. The heteropoly compound of claim 28, wherein When a = 12, b is 0.4-1.0, c is 0.5-1.6, d is 0.1-0.6, e is 0.1-0.6, f is 0.3-1.0, and g is 0.1-0.

6.

44. The heteropoly compound of claim 28, wherein When a = 12, b is 0.5-0.8; c is 0.8-1.2; d is 0.15-0.4; e is 0.15-0.4; f is 0.4-0.8; g is 0.15-0.

5.

45. The heteropoly compound of claim 28, wherein The microwave power was 200-800 W, the temperature was 30-200 °C, and the microwave reaction time was 0.1-5.0 h.

46. ​​The heteropoly compound according to claim 28, wherein The microwave power is 400-800 W, the temperature is 40-150° C., and the microwave reaction is 0.2-4.0 h.

47. The heteropoly compound according to claim 28, wherein The microwave power is 600 W, the temperature is 60-100° C., and the microwave reaction is 0.5-2.0 h.

48. The heteropoly compound according to claim 28, wherein The microwave reaction lasts for 0.8-1.5h.

49. The heteropoly compound according to claim 28, wherein In the first step of the stepwise calcination, the calcination temperature is 180-280° C.; the calcination time is 1-4 hours; and the volume percentage of oxygen is 5-20%.

50. The heteropoly compound according to claim 28, wherein In the first step of the stepwise calcination, the calcination temperature is 200-250° C.; the calcination time is 1.5-3.5 hours; and the volume percentage of oxygen is 5-15%.

51. The heteropoly compound according to claim 28, wherein In the first step of the stepwise calcination, the calcination time is 1.8-3 hours.

52. The heteropoly compound according to claim 28, wherein In the second step of the stepwise calcination, the calcination temperature is 320-440° C.; the calcination time is 1-10 hours; and the volume percentage of oxygen is 30-50%.

53. The heteropoly compound according to claim 28, wherein In the second step of the stepwise calcination, the calcination temperature is 350-400° C.; the calcination time is 2-8 hours, and the volume percentage of oxygen is 30-40%.

54. The heteropoly compound according to claim 28, wherein In the second step of the stepwise calcination, the calcination time is 4-7 hours.

55. Use of the heteropoly compound according to any one of claims 1 to 27 for the oxidation of methacrolein to produce methacrylic acid.

56. A method for preparing methacrylic acid from methacrolein, the method using the heteropoly compound according to any one of claims 1 to 27 as a catalyst.

Citation Information

Patent Citations

  • A heteropolyacid catalyst and its preparation method

    CN103861640B

  • Catalyst for producing unsaturated carboxylic acid as well as preparation method and application thereof

    CN112675912A

  • Heteropolyacid catalyst and application thereof

    CN114160201A

  • Heteropolyacid catalyst and preparation method thereof

    CN104801342A

  • Heteropoly acid salt catalyst and preparation method therefor

    CN105772087A